Hipomineralização molar-inciso em escolares da rede municipal da cidade de Manaus (AM) - Hanan, Simone Assayag [UNESP] (2014)
In order to analyze the prevalence and severity of MIH and its association with dental caries and developmental defects of enamel in the deciduous dentition of public schoolchildren Manaus / AM, we examined 2062 primary school children aged 6-10 years to obtain the MIH, the DMFT, dmft and DDE indexes. The data collected were tabulated and submitted to descriptive statistical analysis by Chi-square, Fisher's Exact and Mann Whitney tests, at a 5% significance level with associations found by odds ratio. The prevalence of MIH in Manaus was 9.12%, and no significant association with gender and age of the children studied was found. The mandibular arch was the most affected, with greater number of teeth being affected on the left side. The most frequently affected teeth were the mandibular permanent first molars, followed by maxillary counterparts and maxillary/mandibular central incisors. The most frequent diagnosis was mild MIH severity. The DMFT of children with MIH was 1.58 and dmft was 2.47, higher than those of the unaffected group and the total sample. A correlation was found between DDE and the presence of MIH. Early diagnosis of MIH is imperative, since the children affected show a high risk for the development of dental caries.